Program Pelatihan Kewirausahaan Digital di Desa Blerong Kabupaten Demak - Yuniarti, Nur Atika; Pramudya, Ryan Arya (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
The community service program is a digital entrepreneurship training program held in Blerong Village. The aim is to increase the ability of MSME players to entrepreneurs using technology, both in collaborating and marketing products. This activity includes knowledge transfer and entrepreneurship training, which takes place at the Computer Laboratory of the Faculty of Economics and Business, University of 17 August 1945 Semarang. This program will be implemented on April 28, 2024, followed by continuous coaching. This training involves resource persons from business practitioners and economic academics. The method used is an educational and participatory approach, which has proven effective in improving the digital skills of MSME owners. The ultimate goal is to help MSMEs achieve business success and increase income through increasing digital entrepreneurial agility.